UTILIZATION OF TECHNOLOGY AS A CREATIVE LEARNING MEDIA AND INNOVATIVE IN THE MILLENIAL GENERATION IN THE NEW NORMAL ERA: A LITERATURE STUDY (International Conference on Social and Islamic Studies, 2021)
This research is a literature review. This study aims to examine the use of technology as acreative and innovative learning medium for the millennial generation in the new normal era.The author uses a qualitative research methodology and the data used comes from relevantliterature studies such as books, journals, theses and websites that can be accounted for forthe correctness of the data. The object of this research is the millennial generation. The results of this study indicate that the use of technology as a creative and innovative learning medium for the millennial generation in the new normal era is very important in the teaching and learning process in order to make it easier for educators to communicate and interact with students inside and outside the classroom. The need for technology in education is not new, the use of technology in this new normal era aims to develop capable and reative students.